Immuno-morphological features of glomerular and tubulointerstitial kidney damage in patients with systemic lupus erythematosus - N A Arzimanova; V V Marasaev; T O Abissova (Научно-практическая ревматология, 2009)
Objective. To assess participation of tubulointerstitial and glomerular components in renal damage progression in pts with systemic lupus erythematosus (SLE) using immuno-morphological data. Material and methods. 45 SLE pts with lupus nephritis, 34 pts with chronic glomerulonephritis (CGN), 19 pts with drug induced chronic tubulointerstitial nephritis (DCTN) and 30 control persons were included. Concentration of anti-DNA antibodies, C-reactive protein (CRP), transforming growth factor β (TGFβ), tumor necrosis factor α (TNFα), monocytic chemotactic protein 1 (MCP1) was evaluated by immunoenzyme assay. Morphological examination of renal biopsies with semiqantitative assessment of measures reflecting process activity, sclerosis and renal blood vessels changes was performed. Results. Elevated concentration of TNFα and CRP was revealed in pts with SLE, CGN and DCTN. Pts with DCTN had highest, pts with CGN – lowest and SLE pts – intermediate values of these measures. There was a clear tendency of TNFα elevation with increase of SLE activity. Pts with lupus nephritis and DCTN had high values of MCP1. TGFβ level was significantly decreased in SLE. Glomerular component of lupus nephritis was characterized mainly by moderate proliferation and sclerosis while tubulointerstitial component signs were prominent. Conclusion. Further examination of tubulointerstitial changes, MCP1 and TGFβ appear to be worthwhile.